2009
DOI: 10.1159/000217860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Fluoride Dentifrice Effect on Enamel Demineralization

Abstract: Although the anticaries effect of fluoride (F) dentifrices is clearly established, the relative importance of F taken up by dental plaque not removed by brushing and of F products (CaF2-like) formed on totally cleaned enamel for the subsequent inhibition of demineralization is not known. Both effects were evaluated using conventional (1,100 μg F/g) and low-F concentration (500 μg F/g) dentifrices in a randomized, crossover, double-blind in situ study. Enamel blocks not treated or pretreated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 45 publications
(26 reference statements)
3
40
0
9
Order By: Relevance
“…23,24 It has recently been shown that the enrichment of remnants of plaque not removed by brushing with fluoride from toothpastes is primarily responsible for its anticaries effect. 25 This means that brushing with fluoride toothpastes is able to protect not only the cleaned surfaces (from which the biofilm was removed), but also the surfaces the toothbrush did not reach. This idea may explain why brushing with a non-fluoride toothpaste, although effective in controlling periodontal inflammation, is not able to significantly reduce caries; to do this, the toothpaste must have fluoride.…”
Section: Individual Methods Of Fluoride Usementioning
confidence: 99%
“…23,24 It has recently been shown that the enrichment of remnants of plaque not removed by brushing with fluoride from toothpastes is primarily responsible for its anticaries effect. 25 This means that brushing with fluoride toothpastes is able to protect not only the cleaned surfaces (from which the biofilm was removed), but also the surfaces the toothbrush did not reach. This idea may explain why brushing with a non-fluoride toothpaste, although effective in controlling periodontal inflammation, is not able to significantly reduce caries; to do this, the toothpaste must have fluoride.…”
Section: Individual Methods Of Fluoride Usementioning
confidence: 99%
“…Such benefits are due to its ability to inhibit the demineralization and enhance remineralization. [3][4][5] A number of studies have suggested that the fluoride released from glass ionomer cements can reduce the demineralization of the surrounding dentin or enamel and favor the remineralization of lesions close to the restoration wall. [6][7][8][9] Glass ionomer cements contain calcium fluoroaluminosilicate glass, which is attacked by polyacids to release cations and fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 However, the extent to which each of these effects influences caries development is unknown, because they are difficult to isolate. Although F toothpaste is able to provide F ions to the oral cavity to interfere with both phenomena, 4,5 its effect when used before or after demineralizing challenges has only been studied in vitro. 1 In this in vitro study, 1 no difference was observed between F toothpaste used to inhibit the demineralization process or to enhance the mineral repair that occurs during the subsequent remineralization.…”
Section: Introductionmentioning
confidence: 99%